Enhancing performance and sustainability of GGBFS-based self-compacting geopolymer concrete blended with coal bottom ash and metakaolin by using RSM modelling - Bheel N.; Alwetaishi M.; Jae I.A.; Syamsir A.; Alraeeini A.S.; Waheeb S.A.; Alkhattabi L.; Benjeddou O. (Nature Research, 2025)
This research study is performed on the self-compacting geopolymer concrete (SCGC) combining coal bottom ash (CBA) and metakaolin (MK) as a substitution for GGBFS alone and combined for analysing the fresh properties (slump flow, V-Funnel, and T50 flow), mechanical characteristics (compressive, splitting tensile and flexural strengths) and durability tests (permeability and sulfate attack test). Though, total 195 SCGC samples were made and tested for 28days. It has been revealed that the consumption of CBA and MK as a substitution for GGBFS alone and combine in the production of SCGC is decreased the workability of SCGC while mechanical characteristics of SCGC are enhanced by utilizing CBA and MK as a substitution for GGBFS alone and combine up to 10%. In addition, the compressive, splitting tensile and flexural strengths were calculated by 59.40MPa, 5.68MPa, and 6.12MPa while using the 5CBA5MK as a substitution for GGBFS in the production of SCGC after 28days correspondingly. Furthermore, the permeability is decreased by growing the quantity of CBA and MK by the weight of GGBFS alone and jointly in the production of SCGC after 28days. Besides, the minimum change in length of the SCGC specimen is recorded by 0.062mm at 7.5MK7.5CBA while the maximum change in length is calculated by 0.11mm at 10CBA10MK as a substitution for GGBFS at 180days correspondingly. In addition, the embodied carbon is recorded reduce as the addition of CBA while it is getting higher when the accumulation of MK alone or combined with CBA in SCGC. Besides, response models for prediction were constructed and confirmed using ANOVA at an accuracy rate of 95%. The models' R2 fluctuated from 88 to 99%. It has been observed that the utilization of CBA and MK alone and together up to 10% as substitution for GGBFS in geopolymer concrete provides the best results therefore it is suggested for structural applications. ? The Author(s) 2024.